Analisis Pengaruh Perbandingan Diameter Inlet dan Oulet Pada Venturi Meter Terhadap Nilai CD - Ramdhan Nugraha Effendi; Oleh Oleh (Peneliti.net, 2023)
Venturi meter is a measuring tool that functions to measure the mass flow rate of fluid flowing in a channel by applying a pressure difference. The pressure difference is generated by the narrowing of the channel from the inlet to the outlet. The difference in the dimensions of the inlet and outlet affect the Coeffeesin discharge Cd value of the measuring instrument. The value of the Cd range from existing standards ranges from 0.90 to 0.97 depending on the Reynolds number experienced by the fluid. From the results of experiments carried out through CFD simulations with several variable ratios of the inlet and outlet dimensions of 0.25, 0.5 and 0.75 with variations in speed of 0.5, 1 and 1.5 m/s. From these results an ideal Cd value of 0.992 was obtained. With the resulting ratio of 0.5.